Thrombocytopenia and neutropenia among extremely low birth weight neonates (Hematology Meeting Reports, 2009)
Thrombocytopenia and neutropenia are common in the NICU, and might be over represented among extremely low birth weight neonates (ELBW, ≤1000g birth weight). However, little is known about these issues in the ELBW population, thus we performed cohort analyses of ELBW neonates in a multihospital healthcare system. Seventy-three percent of patients had one or more platelet counts ≤150,000/uL and 80% of these occurred during the first week. Thrombcytopenia was more common in the smallest patients; 85% in those £800g, 60% in 801-900g, and 53% in 901-1000g. Platelet transfusions were given to 62%, and >90% of these were for patients who were not bleeding. The mortality rate in those receiving platelet transfusions was twice that of those receiving none (p